LATIHAN MENGGUNAKAN ANKLE WEIGHT DAN RUBBER RESISTANCE: DAMPAK TERHADAP KECEPATAN TENDANGAN MAWASHI GERI - Hadjarati, Hartono; Massa, Resa Sukardi; Haryanto, Arief Ibnu; Suardika, I Kadek; Haryani, Meri (Universitas Negeri Surabaya, 2022)
This study aims to determine which is the effect of the more effective exercise between exercises using ankle weights and rubber resistance on increasing Mawashi Geri's kick speed at Karateka Dojo Wadokai, Gorontalo Province. This research is a quasi-experimental research with a two group pretest-posttest research design. The population in this study amounted to 12 Karateka Dojo Wadokai, Gorontalo Province, all of which were samples in this study, then divided into two groups, namely the ankle weight and rubber resistance groups with six samples taken at random in each group. The research instrument used Mawashi Geri kicks by kicking as many targets as possible using the strongest leg for 30 seconds. As a result, this study found that exercise using ankle weights had an average increase of 21% greater than rubber resistance which only had an average percentage of 19%. This study concludes that exercise using ankle weights and rubber resistance can increase Mawashi Geri's kick speed for Karateka Dojo Wadokai, Gorontalo Province.